Failure Analysis of Heat-Exchanger Sheets at Coke Oven - Mohapatra, J. N.; Panda, Arun Kumar; Kumar, D. Satish (Innovation in Science and Technology, 2025)
The heat exchanger sheets at JSW Steel coke oven is 316L used in ammonia stripping / distillation waste water plate heat exchanger (PHE) with the waste water inlet temperature 110oC and outlet temperature 40oC, with water temperature between 35-43oC. The solution include 250mg/liter Ammonical Nitrogen open to atmosphere. The sheets of two heat exchangers, showed pitting/pin holes all over the plates in just 14 days of use after commissioning. Chemical composition of the sheets showed lower Ni (9.3-9.6% against 10%) than the specification. Varying hardness (189-249 Hv0.5 kgf) on the sheets indicating different phases present on the sheets. The analysis revealed the pits are from the top surface (extrusion side) of the plates. SEM-EDS revealed presence of chlorine on the plate, leading to pitting corrosion of the plates. The sheets were checked for their magnetic properties by a permanent magnet showed attracting nature and with a NDE magnetic device the sheets showed magnetic hysteresis loop, indicating presence of magnetic phase (deformation induced martensite) in the sheets. It is inferred that, martensitic transformation from the austenite due to severe plastic deformation has occurred at the manufacturing stage. Hence, galvanic effect caused by the presence of two distinct phases, austenite and martensite, which exhibit different corrosion potentials lead to formation of pitting corrosion due to presence of higher level of chlorides in the water.